A Hybrid Approach: Indirect Electro‐Oxidation Followed by In Situ Electrogeneration of H2O2 in Real Textile Effluent. Issue 4 (18th January 2016) - Aravind, Priyadharshini; Selvaraj, Rajeswari; Sankarmahalingam, Angappan; Kandasamy, Subramanian
Abstract : A two‐step treatment process has been investigated for effective textile effluent management. In step I, the effluent was decolorized via chlorine‐mediated indirect electrooxidation (InDEO), while H2 O2 was electrogenerated during step II in the decolorized textile effluent, by employing an H‐type divided electrochemical cell. The native salts present within the decolorized textile effluent (9.4 g/L Na2 SO4 and 0.8 g/L NaCl) were exploited as electrolytes for the catholyte, whereas 0.5 N sulfuric acid was used as the anolyte for the in situ electrochemical generation of H2 O2 . During the cyclic voltammetry tests, O2 reduction at the activated carbon felt cathode was observed around –0.86 V versus saturated calomel electrode (SCE) at a scan rate of 100 mV/s. Under optimized conditions (cathode potential of –0.9 V vs. SCE and catholyte at pH 6) about 1.45 ± 0.01 mM H2 O2 have been generated. The effluent containing H2 O2 was subjected to Fenton reaction and the generation of OH radicals was confirmed by electron paramagnetic resonance spectroscopy. The results indicated a 59% reduction of the chemical oxygen demand; significant modifications of the functional groups were observed by Fourier transform IR spectroscopy. High performance LC analysis confirmed the degradation of the organic compounds during the oxidative treatment process. These findings suggest the application of this method for degradation of highly colored textile effluents. Abstract : Untreated textile effluent being discharged creates environmental pollution. In the present study, textile effluent is subjected to two‐step treatment processes: Indirect electrooxidation followed by in situ H2 O2 generation. 98% decolorization and 59% COD reduction could be achieved by this method at an energy consumption of 11.13 × 10 −2 kWhm −3 .